The comparative efficiency among communication patterns in solving certain administrative problems in elementary schools - Fabella, Amado 1925-
This experimental study sought to compare the efficiency of four communication patterns--the Circular, the Wheel, the Inverted Y and the ComCon--in problem solving and decision making in terms of speed, messages sent, errors commited, and accuracy. Twenty five-man groups were run, in which group member possessed information not known to other group members of the group and which can only be known by communicating in accordance with prescribed patterns. The difference in the mean scores of the different patterns showed that the ComCon is the fastest, solving the problems in 12 minutes and 39 seconds, faster by 4.1 minutes than the Wheel, the second fastest. However, the Wheel sent the most number of messages and is therefore the least efficient pattern. The Circular committed the greatest number of errors and was the slowest while the ComCon and the Inverted Y arrived at the greatest number of similar and accurate answers.